Analysis of structures and expression patterns of the flavin-containing monooxygenase family genes in Bursaphelenchus xylophilus - HAO Xin; TAN Ruina; CHEN Jie; LI Yang; CAO Jingxin; DIAO Jian; DENG Zhen; ZHANG Ping; MA Ling (浙江大学学报. 农业与生命科学版, 2023)
Flavin-containing monooxygenases (FMOs) participate in endogenous and exogenous metabolisms in organisms, and exist widely in plants, animals and microorganisms. To explore the function of Bursaphelenchus xylophilus FMOs (BxFMOs) in the host colonization and in response to the nematicide stress, we firstly screened and identified 13 Bxfmos from the genome of B. xylophilus by means of bioinformatics, and then analyzed the physicochemical properties, evolutionary development, protein structures, and gene expression patterns of these genes. The results showed that, the Bxfmos distributed on the five chromosomes; their numbers of amino acids were from 432 to 572; their molecular weights were between 49.77 kDa and 66.09 kDa; and their isoelectric points were between 6.26 and 9.27. The structures of BxFMOs were relatively conservative. The gene expression patterns revealed that the BxFMOs had significant effects on the colonization of B. xylophilus and its respondence to nematicidal agents. The above results have important guiding significance and theoretical value for exploring the colonization mechanism of B. xylophilus in the host and seeking the molecular targets to control B. xylophilus.